2019
DOI: 10.3390/min9030169
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of a Pyrite and Arsenopyrite Galvanic Pair in the Presence of Sulfuric Acid, Ferric Ions and HQ0211 Bacterial Strain

Abstract: In this paper, the galvanic effect of pyrite and arsenopyrite during the leaching pretreatment of gold ores was determined with the use of electrochemical testing (open circuit potential, linear sweep voltammetry, Tafel, and electrochemical impedance spectroscopy (EIS)) and frontier orbit calculations. The results show that (i) the linear sweep voltammetry curve and Tafel curve of the galvanic pair are similar to those of arsenopyrite, (ii) the corrosion behavior of the galvanic pair is consistent with that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Thus, the differences in the oxidation rate of arsenopyrite were relatively insignificant (which corresponded to relatively small differences in the concentration of arsenic in the liquid phase), while the oxidation rate of pyrite varied to a greater extent. This may be because arsenopyrite is more easily oxidized than pyrite, and when it is oxidized in a mixture of arsenopyrite and pyrite, electrochemical interactions occur between the minerals which accelerate the oxidation of the arsenopyrite [60,61]. Gold recovery in the control experiment and when using molasses was 92%; when using CO 2 , it was 91%.…”
Section: Concentrate Bio-oxidaton and Gold Recoverymentioning
confidence: 99%
“…Thus, the differences in the oxidation rate of arsenopyrite were relatively insignificant (which corresponded to relatively small differences in the concentration of arsenic in the liquid phase), while the oxidation rate of pyrite varied to a greater extent. This may be because arsenopyrite is more easily oxidized than pyrite, and when it is oxidized in a mixture of arsenopyrite and pyrite, electrochemical interactions occur between the minerals which accelerate the oxidation of the arsenopyrite [60,61]. Gold recovery in the control experiment and when using molasses was 92%; when using CO 2 , it was 91%.…”
Section: Concentrate Bio-oxidaton and Gold Recoverymentioning
confidence: 99%
“…Xu et al [20] investigated the galvanic effect of pyrite and arsenopyrite during leaching of gold ores in sulfuric acid, ferric ion, and HQ0211 bacterial strain solutions with the use of electrochemical testing (open-circuit potential, linear sweep voltammetry, Tafel, and electrochemical impedance spectroscopy, EIS) and frontier orbital calculations. The results indicated that (i) the linear sweep voltammetry curve and Tafel curve of the galvanic pair were similar to those of arsenopyrite, (ii) the corrosion behavior of the galvanic pair was consistent with that of arsenopyrite, and (iii) the galvanic effect promoted the corrosion of arsenopyrite by simultaneously increasing the cathode and anode currents and reducing oxidation resistance.…”
mentioning
confidence: 99%